2016
DOI: 10.1097/ta.0000000000001085
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital lactate improves accuracy of prehospital criteria for designating trauma activation level

Abstract: Background Trauma activation level is determined by prehospital criteria. The American College of Surgeons (ACS) recommends trauma activation criteria; however, their accuracy may be limited. Prehospital lactate has shown promise in predicting trauma center resource requirements. Our objective was to investigate the added value of incorporating prehospital lactate in an algorithm to designate trauma activation level. Methods Air medical trauma patients undergoing prehospital lactate measurement were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 39 publications
1
26
0
1
Order By: Relevance
“…The potential usefulness of prehospital lactate was suggested as a tool for urgent ambulance dispatch for patients with circulatory, respiratory, or neurological disorders 12 , as well as a predictive tool for resuscitative care 13 and designation of trauma activation level 14 . Since the prehospital lactate cost per measurement is not large ($2.00 per measurement) in the study, the study results have high translatability into clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…The potential usefulness of prehospital lactate was suggested as a tool for urgent ambulance dispatch for patients with circulatory, respiratory, or neurological disorders 12 , as well as a predictive tool for resuscitative care 13 and designation of trauma activation level 14 . Since the prehospital lactate cost per measurement is not large ($2.00 per measurement) in the study, the study results have high translatability into clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…26 Closing this critical knowledge gap would enable resuscitation to be titrated to reduce both risk of rebleeding and optimize tissue perfusion. Although no such technology currently exists, advanced in computer-generated decision support tools utilizing continuous vital sign measures, tissue oxygen saturation monitoring, 27 and serial lactate measurements 28 have all demonstrated promising early results.…”
Section: Remote Damage Control Resuscitation (Rdcr)mentioning
confidence: 99%
“…Reliance on vital signs and physical exam however, has been reported to miss patients with serious injury [1]. Point of care (POCT) serum lactate measurement is emerging as an adjunct to pre-hospital clinical assessment and has the potential to guide triage and advanced treatment decision-making: pre-hospital lactate levels have been shown to predict the need for resuscitative inhospital care in trauma patients [2][3][4][5], and to predict outcome of trauma patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many pharmacological and non-pharmacological) treatments on scene have the potential to modulate beta adrenergic stimulation, and thereby influence lactate levels. Although this will not affect the prognostic ability of elevated prehospital lactate levels as such (several studies have shown that the prognostic ability of lactate exceeds the prognostic ability of markers of end organ hypoperfusion) [2][3][4][5], it might influence the use of lactate as a marker to guide advanced prehospital treatments such as blood product transfusion [8].…”
Section: Introductionmentioning
confidence: 99%